2017
DOI: 10.1007/s12035-017-0821-y
|View full text |Cite|
|
Sign up to set email alerts
|

Protein Biomarkers and Neuroproteomics Characterization of Microvesicles/Exosomes from Human Cerebrospinal Fluid Following Traumatic Brain Injury

Abstract: Recently, there have been emerging interests in the area of microvesicles and exosome (MV/E) released from brain cells in relation to neurodegenerative diseases. However, only limited studies focused on MV/E released post-traumatic brain injury (TBI) as they highlight on the mechanistic roles of released proteins. This study sought to examine if CSF samples from severe TBI patients contain MV/E with unique protein contents. First, nanoparticle tracking analysis determined MV/E from TBI have a mode of 74-98 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 44 publications
2
103
1
Order By: Relevance
“…The 16 articles selected fall into two main categories: 8 clinical papers and 8 laboratory studies on animal models of TBI [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Briefly, the 8 clinical studies identified have described four main technologies for identification of predictive biomarkers: (a) Microvescicle/Exosome, (b) MicroRNA, (c) Mass Spectroscopy, and (d) Multiplexing and Immunoassays [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 16 articles selected fall into two main categories: 8 clinical papers and 8 laboratory studies on animal models of TBI [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Briefly, the 8 clinical studies identified have described four main technologies for identification of predictive biomarkers: (a) Microvescicle/Exosome, (b) MicroRNA, (c) Mass Spectroscopy, and (d) Multiplexing and Immunoassays [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study examined exosomes, isolated from human CSF following TBI, using a proteomics approach [ 8 ▪▪ ]. Exosomes or microvesicles/exosomes (MV/E) are released from brain cells during disease and injury.…”
Section: Progress To Date In 2018mentioning
confidence: 99%
“…These packages actively contribute in inflammatory processes by interacting with immune cells, epithelial and endothelial cells, and bridging innate and adaptive immunity ( 19 , 20 ). Several studies showed that MV numbers and their origin are altered in trauma and sepsis ( 21 23 ). Patients with major burn injury showed elevated numbers of granulocyte- and monocyte- derived MVs, and this increase was associated with injury severity ( 24 ).…”
Section: Introductionmentioning
confidence: 99%